THE TRANSLATION OF PHRASAL VERBS IN THIRTEEN REASONS WHY - Ance Elsy Saragih; Syahron Lubis; Muhizar Muchtar (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2020)
The form of a phrasal verb may be the same but they bear different meanings in accordance with the context of situation. The dynamics of language also influence the change of phrasal verb meanings. This paper presents the problems faced by the translator in translating several phrasal verbs in the novel Thirteen Reasons Why by applying the theory of Ghazala in which it is stated that phrasal verbs are linked with the lexical problems and stylistics. Lexical problems coccur when a word, a phrase or an expression is not understood clearly and directly, misunderstood, not known at all to translators, or not found in standard dictionaries, while stylistic problems, righty seen as a part of meaning strongly affect  the style of source language posing problems for the translator as the styles of the ST and TT could not  be easily adjusted to similarity.  The data in the forms of phrasal verbs are taken from the source language and in the target language, supported by the descriptive qualitative method. The results of show that the problems in translating the phrasal verbs in the novel lie in lexical words (literal meaning, synonymy, polysemy, and idiom) and stylistics (formality and informality of language)